Singapore Management University Report to Stakeholders 2012 - 2013 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
The report features an article written by our chairman, Mr Ho Kwon Ping. Entitled ‘The Challenges Ahead’, he shares his thoughts on the future of SMU – the transformational change it must embrace, and the serious deliberation it must undertake if it were to develop into a small and comprehensive university. SMU President Professor Arnoud De Meyer in his State of the University Address 2013 gave a thorough update on the outstanding achievements of our students, faculty and staff, noting that the "want something, do something” culture he had encouraged a year ago is gaining strong momentum. Looking ahead, he invited the SMU community to join him “in writing our next success story”.